If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v + -15 = (-27) Reorder the terms: -15 + v = (-27) -15 + v = -27 Solving -15 + v = -27 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + v = -27 + 15 Combine like terms: -15 + 15 = 0 0 + v = -27 + 15 v = -27 + 15 Combine like terms: -27 + 15 = -12 v = -12 Simplifying v = -12
| 395x-40=8x+2 | | m-9=(-13) | | -685/85= | | m+4=(-12) | | 2(2x+4)=0 | | 3-1/2r=9/2 | | m/5-3=22 | | 5(x+5)/3=6x-1 | | -3/8-1/10 | | 3(c-1)=2c-5 | | 15-3(x+4)=9 | | x/2+4=x/4-1 | | -4+7y=-9y+4 | | 6(3x-2)=2+4x | | x/3+5=x/6-6 | | 5x+6-3x=3x-2 | | Ln(3x^2+5x)=ln(6x+10) | | e=.046+[e(.091)-.046]1.46 | | 2x^3-x^2-X=5 | | -X+2=X-3 | | Ln(2x)=6 | | y(2y+y-3y+6)= | | 50=w+28 | | -3x^2+12+16x=0 | | 13+a=26 | | graph-4x+2y=8 | | c+93=171 | | 3(6x-1)/2(x-1) | | 5(-1/5)+1=0 | | 72=h+48 | | 44=42+k | | 50+x+3=180 |